Respuesta :

eric

Hey! Great to see you again.

Based on what we learned last time, we can apply it to this equation!

Solve 3x+y =−5 for y:

3x+y=−5

3x+y+−3x=−5+−3x Let us add -3x to both sides.

y=−3x−5.

Substitute −3x−5 for y in −2x+3y=18:

−2x+3y=18

−2x+3(−3x−5)=18

−11x−15=18 Simplify both sides :)

−11x−15+15=18+15 Add 15 to each side.

−11x=33

x = -3

Now solve for y.

−3 for x in y=−3x−5:

y=(−3)(−3)−5

Can you solve this equation? Let me know if you need help, tell me what you get! :) That will be your y answer. :D

Have a great one!